Arktische Kohle. Das sowjetische Engagement auf Spitzbergen, 1928-1949 - Frey, Felix (Schwabe, 2018)
To diversify the USSR’s energy supply, a major objective of the Stalinist command economy, Soviet workers were sent to Norway’s Svalbard (Spitzbergen) archipelago in 1931 to mine coal. Drawing on archival materials, this paper discusses the complex entanglement this resource extraction meant for Moscow, the Kola Peninsula, and Svalbard. The archipelago was by no means an Arctic sideshow: miners flooded the streets of Murmansk, in far northwest Russia, awaiting their departure to the archipelago, and Svalbard coal fueled the furnaces of the Kola Peninsula Murmansk is located on. Officials in distant Moscow tried to regulate the oft-problematic circulation of coal and workers, in the process reconfiguring the understanding of how coal and miners were interrelated both technically and socially. In 1946, matters reversed due to changed geopolitical objectives. Rather than having miners dig coal to be sent to Russia, the war-ravaged mines were rebuilt; now workers were sent to Svalbard in order to strengthen Soviet claims on the territory.